Implementation of calculation and deduction of income tax article 23 on train washing contracting and on trip cleaning PT. KAI DAOP 9 Jember in the perspective of Islamic economics. - Azizi, Muhammad Naufal; Siswanto, Adil (Journal of Commerce, Management, and Tourism Studies, 2025)
The main focus of this research is to find out how the mechanism for calculating and deducting Income Tax Article 23 is carried out, and to what extent its implementation mids accordance with the tax regulations in force in Indonesia. This research uses a qualitative approach with a case study method. Data collection techniques by direct field observation, in depth interviews with internal company personnel, and documentation of relevant tax documents. The results of the study show that PT. KAI DAOP 9 Jember has implemented the mechanism for calculating and deducting Article 23 Income Tax with a rate of 2% of the gross amount in accordance with the provisions of Minister of Finance Regulation No. 141/PMK.03/2015. The tax payment process is carried out through the e-Billing system, while reporting uses the e-Bupot application provided by the Directorate General of Taxes. The conclusion of this research sos PT. KAI DAOP 9 Jember has implemented a mechanism for calculating and deducting Article 23 Income Tax for the contracting of train washing and on Trip Cleaning services by following applicable tax provisions.